Trust-Based Authentication for Secure Communication in Cognitive Radio Networks - Parvin, Sazia; Han, Song; Tian, Biming; Hussain, Farookh Khadeer (IEEE, 2010)
Over the past few years, Cognitive Radio (CR) has been considered as a demanding concept for improving the utilization of limited radio spectrum resources for future wireless communications and mobile computing. Since a member of Cognitive Radio Networks may join or leave the network at any time, the issue of supporting secure communication in CRNs becomes more critical than for the other conventional wireless networks. This work thus proposes a secure trust-based authentication approach for CRNs. A CR node’s trust value is determined from its previous trust behavior in the network and depending on this trust value, it is decided whether or not this CR node will obtain access to the Primary User’s free spectrum. The security analysis is performed to guarantee that the proposed approach achieves security proof.